Advances in personalized gastroenterology and hepatology 2016 - E. Blum Hubert (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Molecular and cell biology have resulted in major advances in our understanding of disease pathogenesis as well as in novel strategies for the diagnosis, therapy and prevention of human diseases. Based on modern molecular, genetic, epigenetic microbiologic and biochemical analyses it is, on the one hand, possible to identify disease-related point mutations and single nucleotide polymorphisms in the context of genomewide association analyses (GWAS). On the other hand, using high throughput array and other technologies, it is possible to simultaneously analyze thousands of genes (DNA) or gene products (RNA and proteins), resulting in an individual gene or gene expression profile (‘signature’) or to characterize the individual microbiome and its pathogenetic potential. Such data increasingly allow to define the individual disease predisposition or risk and to predict disease prognosis as well as the efficacy of therapeutic strategies in the individual patient (‘personalized medicine’). All these aspects have greatly contributed to the recent advances in the diagnosis, treatment and prevention of human diseases.